A proposed design model for blended education depending on the E-learning evaluation model compared to regular education in universities, based on the viewpoint of the beneficiaries - Osama gazi (Journal of Madenat Alelem University College, 2023)
The aim of the current research is to design a model to evaluate e-learning compared to formal education in Iraqi universities from the beneficiaries' point of view, identify the advantages and disadvantages of e-learning, and propose a design for blended learning based on the results of this study.By verifying the hypothesis, the research sample of Iraqi university students' attitudes about e-learning was surveyed, and the factor analysis of the correlation coefficients between the questionnaire questions revealed one general component and many collective factors regarding the benefits and drawbacks of e-learning. The research sample consisted of (100) teachers and (200) students from five Iraqi universities.A questionnaire consisting of (30) items was used to identify the opinions of the research sample regarding e-learning and traditional education. The data was analyzed using the rotation of factors using the Varimax Method.The results showed eight dimensions around which the negatives and positives of electronic and traditional education revolve.Based on the results, the researchers proposed a new model for blended learning that can be used in Iraqi universities according to their available capabilities.